UV-responsive fluorescent behavior of pharmaceuticals assessed by UV-induced fingerprint spectroscopy (UV-IFS) - Pavelicova, Kristyna; Rypar, Tomas; Markova, Katerina; Mravec, Filip; Adam, Vojtech; Vaculovicova, Marketa; Nejdl, Lukas (International journal of pharmaceutics, 2022)
UV-induced fingerprint spectroscopy (UV-IFS), a new tool in a toolbox of analytical methods, is a powerful technique registering molecule-specific changes of fluorescence induced by UV irradiation. Analysis of fluorescence spectra of a sample prior and after UV irradiation enables an identification of a sample of a drug or pharmaceutics based on a comparison with signals of known standards. Moreover, UV-IFS uncovers the presence of undesired contaminations or intentional changes of the composition. Herein, we employ UV-IFS for qualitative as well as quantitative analysis of common medicines including analgesic/antipyretic (Acetaminophen), antihistamines (Loratadine and Desloratadine), and phosphodiesterase type 5 inhibitors (Tadalafil and Sildenafil citrate). UV irradiation (λem = 254 nm) for 2 - 10 min induced significant changes of fluorescence of the studied samples and according to the unique patterns, the quality and quantity were evaluated. Limits of detection for individual active ingredients were calculated as follows: Acetaminophen = 0.1 μg·mL-1, Loratadine = 0.1 μg·mL-1, Desloratadine = 0.01 μg·mL-1, Tadalafil = 0.04 μg·mL-1 and Sildenafil = 0.2 μg·mL-1. Moreover, genuine and fake CIALIS, VIAGRA and KAMAGRA tablets were reliably identified.
Keywords: paracetamol; Tablets; spektrální analýza; Sildenafil Citrate; loratadin; Acetaminophen; Spectrum Analysis; tadalafil; sildenafil citrát; Loratadine; Tadalafil; tablety